2017
DOI: 10.1016/j.physio.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Updated reliability and normative values for the standing heel-rise test in healthy adults

Abstract: The heel-rise test is highly reliable. The regression models herein can be employed by clinicians to evaluate the outcomes of heel-rise tests of individuals against a comparable normative population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 37 publications
3
73
0
7
Order By: Relevance
“…Jarnlo & Nordell used it in a methodological study on a balance performance test on elderly people and Mosallanezhad et al when comparing physical activity and physical functioning in 75‐year‐old‐Swedish and Iranian persons. Lindskov et al used it on patients with Parkinson's disease and Hébert‐Losier et al to describe their participants as for their analysis in a study on the heel‐rise test in healthy adults. A Norwegian study included the scale in a study on fear‐avoidance beliefs and pain in 60 to 86‐year‐old patients with leg ulcers .…”
Section: Resultsmentioning
confidence: 99%
“…Jarnlo & Nordell used it in a methodological study on a balance performance test on elderly people and Mosallanezhad et al when comparing physical activity and physical functioning in 75‐year‐old‐Swedish and Iranian persons. Lindskov et al used it on patients with Parkinson's disease and Hébert‐Losier et al to describe their participants as for their analysis in a study on the heel‐rise test in healthy adults. A Norwegian study included the scale in a study on fear‐avoidance beliefs and pain in 60 to 86‐year‐old patients with leg ulcers .…”
Section: Resultsmentioning
confidence: 99%
“…The PENS is always used with the therapeutic aim of relieving chronic pain and neuropathic pain, improving cervical ROM or improving muscular activity in the sport . Khan et al suggested that improving muscular strength may be a way to prevent these injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The test also shows "excellent" reliability for pediatric patients aged 6 years and older. [70][71][72][73][74]…”
Section: Heel Rise Test: Diagnostic Testmentioning
confidence: 99%